Penggunaan Near Infrared Spectroscopy untuk Evaluasi Kaki Diabetes: Analisis - Kartika, Ronald; Timotius, Kris Herawan (PT Kalbe Farma Tbk., 2025)
Introduction: Diabetic foot disease requires serious management due to the risk of amputation. Microvascular abnormalities increase the risk of amputation by impairing blood flow, slowing wound healing, and increasing the risk of infection. Methods: Systematic review of the clinical potential of near infrared spectroscopy (NIRS) for identification of peripheral arterial disease (PAD) concomitant with diabetic (DM) microangiopathy. Systematic literature search through PubMed BMC Central published in 2018-April 2024. Discussion: NIRS can provide clues such as prediction of recovery time, deoxygenation of peripheral blood, oxygen consumption (VO2), tissue oxygen saturation (StO2), total hemoglobin (HbT), and oxyhemoglobin area under the curve (O2 HbAUC). NIRS has the potential to help predict wound healing especially in diabetic patients with symptoms masked by peripheral neuropathy. Conclusion: NIRS can assess the effectiveness of treatment and prevent worsening PAD in diabetic foot.